Increased levels of anti-dsDNA antibodies in immune complexes before treatment with belimumab associate with clinical response in patients with systemic lupus erythematosus - Azita Sohrabian; Ioannis Parodis; Nellie Carlströmer-Berthén; Martina Frodlund; Andreas Jönsen; Agneta Zickert; Christopher Sjöwall; Anders A. Bengtsson; Iva Gunnarsson; Johan Rönnelid (Arthritis Research & Therapy, 2019)
Abstract Introduction Immune complexes are of importance in systemic lupus erythematosus pathogenesis, and autoantibodies are believed to participate in immune complex formation. Quantification of autoantibody levels in circulating IC might be of prognostic value. Methods A C1q-binding-eluting technique was applied to purify immune complexes from 55 belimumab-treated systemic lupus erythematosus patients during a 24-month follow-up. Autoantibodies in serum and in solubilized immune complexes were quantified using addressable laser bead immunoassay. We investigated whether levels of autoantibodies in immune complexes associate with disease activity and response to belimumab treatment. Results High baseline anti-double-stranded DNA and anti-histone levels in immune complexes associated with attainment of zero scores in clinical systemic lupus erythematosus disease activity index 2000 during the 24-month follow-up (p = 0.003 and p = 0.048, respectively). Low complement levels associated with high serum anti-double-stranded DNA and anti-ribosomal P levels (p = 0.003 and p = 0.008, respectively) and high anti-double-stranded DNA (p = 0.002) but not anti-ribosomal P levels in immune complexes. Anti-SSA/SSB serum levels were lower in patients attaining lupus low disease activity state at month 6; these associations were stronger for corresponding immune complex levels. Serum levels of most autoantibodies had declined at month 3, whereas autoantibody levels in immune complexes, except for anti-double-stranded DNA, showed a more gradual decline over 1–2 years. Serum anti-double-stranded DNA levels decreased in all patients irrespective of systemic lupus erythematosus disease activity index 2000=0 attainment, whereas immune complex levels decreased only in achievers. Conclusion Immune complex levels of autoantibodies against double-stranded DNA and the SSA/SSB complex show more specific associations with treatment outcome compared with serum levels in belimumab-treated systemic lupus erythematosus patients. Characterization of autoantibody content in circulating immune complexes could prove useful in treatment evaluation in systemic lupus erythematosus and other immune complex-associated diseases.